PERBANDINGAN PENGARUH METODE LATIHAN ACCELERATION SPRINTS, HOLLOW SPRINTS ,DAN REPETITION SPRINTS TERHADAP PENINGKATAN PRESTASI LARI 100 METER DITINJAU DARI KLASIFIKASI TINGGI-BERAT BADAN - JASMANI JASMANI (Universitas Tunas Pembangunan, 2012)
The purposes of this study are investigating of : (1) the effect comparation among the acceleration sprints, hollow sprints, and repetition sprints training methods to the increasement of a hundred meters running acheivement, (2) anincreasement comparation of a hundred meters running achievement between a group who has the minus normal weight and the plus one, (3) the interaction effects between training methods and the body’s weight. The increasing of a hundred meters running achievement is computed by substracting the initial test score with the final one.The body’s weight classification was determined by considering the weight of the body and the height. This research used the experimental method with 3 X 2 factorial design. The sixty college students of The Tunas Pembangunan University as samples. They were divided into six experimental groups andwere drawn by random sampling technique. There wastwo independent variables and a dependent variable. Dependent variable was as a response variable. It was an increasement of a hundred meters running acheivement. The first independent variable was training methods, with three levels. They were acceleration sprints, hollow sprints, and repetition sprints. The second was body’s weight, with two levels, the minus normal body’s weight and the plus one. This study was held in The Tunas Pembangunan University, Surakarta. The technique for gathering the data used test and measurement.They were a hundred meters running test, the body’s weight and body’s height measurements.Whereas for analyzing the data used The Two Ways Analysis of Variance. All statistical computation and analysis used Statistical Software Minitab 16. The results of this study show :to the increasement of a hundred meters running acheivement: (1) There was a significant difference of the effect amongacceleration sprints, hollow sprints, and the repetition sprints training method. The effect of the second training method was the best one. Fobs = 3,36, p = 0,042. The average of a hundred meters running achievement with hollow sprints treatment was 0,361 secons(2)There was a significant difference a hundred meters running achievement between the minus normal body’s weight group and the plus one. Fobs = 16,73, p = 0,000. The minus normal body’s weight group’s achievement was better than the plus one. On the minus normal body’s weigh group, average score of achievement was 0,373, while the plus normal body’s weight group was 0,246. (3) There was interaction between the training methods and body’s weight. Fobs = 3,58, p = 0,035. The minus normal body’s weight group with acceleration sprints training method got the best achievement with average score 0,416, while the plus normal body’s weight group with acceleration sprints training method got the lowest, with average score 0,193.